2019
DOI: 10.1099/jgv.0.001174
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factors 3 and 7 have distinct roles in the pathogenesis of alphavirus encephalomyelitis

Abstract: Interferon (IFN) regulatory factors (IRFs) are important determinants of the innate response to infection. We evaluated the role(s) of combined and individual IRF deficiencies in the outcome of infection of C57BL/6 mice with Sindbis virus, an alphavirus that infects neurons and causes encephalomyelitis. The brain and spinal cord levels of Irf7, but not Irf3 mRNAs, were increased after infection. IRF3/5/7À/À and IRF3/7À/À mice died within 3-4 days with uncontrolled virus replication, similar to IFNa receptordef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 123 publications
(154 reference statements)
1
9
0
Order By: Relevance
“…GABPA is essential for human cognition (Reiff et al, 2014). IRF3 is related to brain disease (Schultz et al, 2019). PPAR, which PPARG belongs to, is believed to be the therapeutic target of neurodegenerative diseases (Warden et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…GABPA is essential for human cognition (Reiff et al, 2014). IRF3 is related to brain disease (Schultz et al, 2019). PPAR, which PPARG belongs to, is believed to be the therapeutic target of neurodegenerative diseases (Warden et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…GABPA is essential for human cognition (16). IRF3 is related to brain disease (18). PPAR, which PPARG belongs to, is believed to be therapeutic target of neurodegenerative diseases (53).…”
Section: Resultsmentioning
confidence: 99%
“…As we have previously found TF mutants to have altered virion morphology secondary to aberrant budding (11), we wanted to investigate in vivo trafficking defects as a possible explanation for this loss of virulence. We employed a second well-established model of infection, IC infection of young C57BL/6 mice (50,51). Again, we found that all three mutant viruses had severely attenuated virulence in WT mice ( Figure 2C).…”
Section: Palmitoylation Of Tf Is a Critical Virulence Determinant Prmentioning
confidence: 97%